Carbon footprint, demography, and employment status? - Henrik Carlhoff (Universität Rostock, Institut für Volkswirtschaftslehre, 2019)
This paper investigates the interplay between aging of a society and its carbon dioxide emissions. The existing literature based on US data predicts lower overall emissions due to the lower emission intensity of consumption of a growing old-age share of the population. This conjecture is reexamined by a multivariate approach. The underlying hypothesis is that the individual levels of emissions do not only depend on age but also on income and employment status, which are correlated with age. Thus, bivariate analyses, neglecting other relevant variables, might overstate the decline in emissions for older cohorts. The paper shows that this hypothesis is correct. A bivariate approach overestimates the decline of emissions caused by population aging. Policy decisions favoring a longer work life may reverse the dampening effect of aging on emissions.
Keywords: J11; Q54; 330